(untitled) (Altre Modernità, 2018)
Fanfiction, a specific type of digital literature, is a phenomenom that must be studied deeply, particularly in its relationship with author’s issues. This essay aims to present a general overview of fanfiction in Spanish. Then, it analizes some of the usual paratexts which appear in this kind of production to illuminate the debates about the “author’s death”. The analysis pretends to show how the affective bond between authors and readers is a fundamental element in this genre.